(untitled) (Faridpur Medical College Journal, 2021)
SARS-CoV-2 corona virus infection (COVID-19) is a public health emergency of international concern causing many deaths. The aim of this study was to assess demography, clinical presentation, blood group, disease severity and outcome of COVID-19 infected patients in Bangladesh. This is a cross sectional, observational study of 436 COVID- 19 infected patients, confirmed by RT-PCR assay’s on nasopharyngeal swab specimens, presented at Faridpur Medical College Hospital and Kurmitola General Hospital during the month of May to September, 2020. Data were collected in a preformed data sheet and analyzed for variables included demography, source of infection, spreading within family, clinical features, blood group, disease severity and outcome. Study showed mean age 41.27±16.65 years with slight male predominance (1.87:1), most were service holder (47%), source of infection was unknown (40%), from infected family members (35%) and working place (23%). In 44% cases, family members of infected index cases were unaffected. Common co-morbidities were Diabetes Mellitus (19.7%) and Hypertension (19%). Blood group of most (41.29%) was B positive. Disease spectrum ranged from asymptomatic (15%), mild (53%), moderate (19%) and severe (13%) disease. Common presenting symptoms were fever (72.2%), cough (42.9%) dyspnoea (29.6%), myalgia (22.9%), anorexia (17.9%), fatigue (17.4%), diarrhea (13.5%), headache (12.4%) and anosmia (12.4%). Majority (75.2%) had nonspecific (fever, mayalgia, fatigue) symptoms and in 16.28% cases it was the only presentation. Respiratory (61.9%) and GI (28.4%) symptoms presented either concomitantly or with nonspecific symptoms (55%). Majority (95%) of patients recovered and only 5% died. Faridpur Med. Coll. J. Jan 2020;15(2): 53-57